Client Governing Success Criteria in Building Information Modelling (BIM)-Based Projects - Hadzaman, Nor Asma Hafizah; Takim, Roshana; Nawawi, Abdul Hadi (International Journal of Sustainable Construction Engineering and Technology, 2020)
Building Information Modeling (BIM), also known as n-D Modeling is a revolutionary development in the Architecture-Engineering-Construction (AEC) industry that consists of both technology and process. BIM helps project stakeholders in communicating complex, technical and difficult to visualise project elements that not easily explained. Nevertheless, there is a lack of overall governance within the current projects environment. A successful BIM implementation needs the involvement of behavioural, cultural and technological changes to transform the organisation into BIM-based projects through adopting new processes and standards. Thus, it is inevitable to develop a governance solution to facilitate BIM adoption in a collaborative working environment across project lifecycle. This paper discusses a success measure of BIM-based projects in Malaysia. The methodology is based on a qualitative research technique and the method is through a well-planned brainstorming workshop. All data were analysed using Atlas t.i. version 8. The findings revealed that four (4) success measures of BIM-based projects are: socio-organisational, legal, technical, and financial. It is anticipated that the findings reported in this paper could provide an insight for future strategies and guidelines for the development of BIM projects in Malaysia. BIM governance framework proves to be valuable for project stakeholders in managing collective efforts to standardise construction processes.